Online Marketing Enterprise of Jombang Culinary from TAM and VEM Perspective on Social Media - purwanto, nuri; Juwita, Kristin (Bina Nusantara University, 2017)
The purpose of this research was to develop, evaluate, and test antecedent model with trust as an intermediary variable of Technology Acceptances Model (TAM) and Virtual Experiential Marketing (VEM) for buying intention. It used purposive sampling technique with 300 respondents. The questionnaire results were evaluated and analyzed using Structural Equation Model (SEM) method with the analysis tools (the third version of SmartPLS). The research result shows that there is no effect between TAM and trust. In addition, there is a direct and positive influence of VEM on trust. The trust and TAM have a positive effect on buying intention. However, VEM does not affect buying intention. The results indicate that the trust cannot mediate TAM and buying intention. Meanwhile, trust can mediate between VEM and buying intention.